Characterization of the single-stranded DNA binding protein pVVGJΦ of VGJΦ phage from Vibrio cholerae - Falero, Alina; Caballero, Andy; Trigueros, Sonia; Pérez, Celso; Campos, Javier; Marrero, Karen; Fando, Rafael (Biochimica et biophysica acta. Proteins and proteomics, 2011)
pVVGJΦ, a single-stranded DNA binding protein of the vibriophage VGJΦ was subject to biochemical analysis. Here, we show that this protein has a general affinity for single-stranded DNA (ssDNA) as documented by Electrophoretic Mobility Shift Assay (EMSA). The apparent molecular weight of the monomer is about 12.7kDa as measured by HPLC–SEC. Moreover, isoelectrofocusing showed an isoelectric point for pVVGJΦ of 6.82 pH units. Size exclusion chromatography in 150mM NaCl, 50mM sodium phosphate buffer, pH 7.0 revealed a major protein species of 27.0kDa, suggesting homodimeric protein architecture. Furthermore, pVVGJΦ binds ssDNA at extreme temperatures and the complex was stable after extended incubation times. Upon frozen storage at −20°C for a year the protein retained its integrity, biological activity and oligomericity. On the other hand, bioinformatics analysis predicted that pVVGJΦ protein has a disordered C-terminal, which might be involved in its functional activity. All the aforementioned features make pVVGJΦ interesting for biotechnological applications. ► pVVGJΦ a DNA binding protein of phage VGJΦ has a general affinity for ssDNA. ► SEC revealed a major species of 27.0kDa, suggesting a homodimeric protein. ► pVVGJΦ binds ssDNA at extreme temperatures, stable after extended times. ► After a year at –20°C the protein kept its biological activity and oligomericity. ► pVVGJΦ is interesting and attractive for further application in biotechnology.